Acoustic emission analysis for bearing condition monitoring - Mohd Helmi, Rasid (2013)
Acoustic emission (AE) was originally developed for non-destructive testing of static structures, however, over the years its application has been extended to health monitoring of rotating machines and bearings. It offers the advantage of earlier defect detection in comparison to vibration analysis. Current methodologies of applying AE for bearing diagnosis are reviewed. The investigation reported in this paper was centered on the application of standard acoustic emissions (AE) characteristic parameters on a rotational speed. An experimental test-rig was designed to allow seeded defects on the inner race, corrode and contaminated defect. It is concluded that irrespective of the rotational speed and high levels of background noise, simple AE parameters such as amplitude and AE counts provided an indications of bearing defect. In addition to validating already established AE techniques, this investigation focuses on establishing an appropriate threshold level for AE counts.